Design of Matched Absorbing Layers for Surface Plasmon-Polaritons. (29th August 2012) - de la Cruz, Sergio; Méndez, Eugenio R.; Maradudin, Alexei A.
Abstract : We describe a procedure for designing metal-metal boundaries for the strong attenuation of surface plasmon-polaritons without the introduction of reflections or scattering effects. Solutions associated with different sets of matching materials are found. To illustrate the results and the consequences of adopting different solutions, we present calculations based on an integral equation formulation for the scattering problem and the use of a nonlocal impedance boundary condition.